The development of a broadcasting - Satyendra Kumar (Journal of All India Institute of Speech and Hearing)
The purpose oi the present study was to develop a hearing screening test, a single administration of which, would screen a large Dumber of people even without the need for their coming to a speech and hearing center. It was intended that the test be of such a nature that it may be broadcast over the radio and all the persons listening to the radio may be screened out for any hearing impairments. This test would provide for an efficient tool for hearing screening which would not require any special equipment or testing environment and would test a large number of people in one administration of it. It would even be possible to test difficult-to-reach individuals by means of this test. Moreover, no trained personnel would be required for the administration of the screening test.